Analisis Gaya Bahasa Melalui Buku Dongeng Si Kancil yang Cerdik Sebagai Alternatif Bahan Ajar - Islamiyati, Nurul; Wardana, Deni; Widjojoko, Widjojoko (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Learning materials are various forms of materials that function to support teachers in the teaching teams in the teaching and learning process in the classroom. The purpose of this study is to analyze the style of language through fairy tale book Si Kancil yang Cerdik as an alternative teaching material to write poetry for fourth grade students. In this study using qualitative approach by applying content analysis method. The subject of this study was the stylistic style of the clever picture book. The results of the study that has been done obtained 115 sentences that use the style of language in a fairy tale book. There are 19 types of language styles, them are comparative language styles (parables, metaphors, personification, allegories (fables), antithetic, pleonasm and tautology, periphrasis, and correction or epanorthosis), oppositional language styles (hyperbole, irony, apostrophes, cynicism, and sarcasm), linking language styles (metronomic, synced, epithets, and ellipticals), and iteration language styles are mesodilopsis. From the data, there are 7 categories that describe what the author wants to convey, such as the atmosphere, circumstances, feelings, actions, figures, attitudes, and time that are then used as teaching materials in the form of handouts containing poetry writing materials, language styles for teacher handles and student worksheets as an exercise in understanding language styles and writing poetry.